Surveying healthcare workers to improve the design, wearer experience and sustainability of PPE isolation gowns - Šterman, Sonja (Strojniški vestnik, 2022)
This protective clothing design project responds to the urgent need for research into the redesign of personal protective equipment (PPE) isolation gowns, to be more fit for purpose and reusable to enhance the experiences of healthcare workers treating patients with COVID-19 and variants. Funded by the Arts and Humanities Research Council (AHRC) the research addresses the engineering question: “What new materials, design and manufacturing approaches should we start to consider in preparation for pandemics e.g. reusable PPE to replace single use?” The article focuses on the online questionnaire/ survey, its main findings and the ‘participatory clothing design’ methodology which prioritises the lived experiences and expressed needs of healthcare workers wearing disposable and reusable PPE in acute care scenarios. Research methods include literature and gown reviews, selected interviews and survey directed at nurses, to acquire first-hand qualitative data about the impact of current gown design and procurement policies on wearers. Selected results and commentary from the ongoing survey are presented and thematically analysed to inform the development of reusable gowns. Semi-structured interviews with clinical leads and caregivers, as well as responses from users, will be important to integrate expertise in fashion, textile and uniform design, clinical practice, and manufacturing. Further design will be based on a complex design brief that balances the needs of wearers and critical care providers while considering regulations, protection, comfort, sustainability, and cost. This research focuses on enhancing an overlooked area of critical care clothing and the people who wear it while reducing its detrimental impact on the planet.
Keywords: ankete; healthcare workers; isolation gowns; izkušnje uporabnika; izolacijske obleke; kvalitativno raziskovanje; oblačila za večkratno uporabo; qualitative research; reusable PPE; surveys; wearer experience; zdravstveni delavci